Understanding the City: Its Conception and History - Ahmadin (Jurnal Ekonomi dan Riset Pembangunan, 2023)
The existence of a city concerning the dynamics of growth and the complexity of the problems that accompany its progress have always been an interesting topic in the study of various scientific disciplines. Specifically within the scope of social science studies, there are urban history, urban sociology, urban spatial sociology, urban anthropology, and others. Various studies with a multidisciplinary approach to the city require an understanding of the concept and a brief history of its origins as a scientific basis for the development of its studies. This article examines the basic concept of the city and its brief history, which begins with a discussion of the meaning, origins of cities, urban forms, urban development, and problems that arise in urban areas. The results of the study show that cities have various meanings from the point of view of scientists from various scientific disciplines. Historians, sociologists, economists, geographers, architects, and artists give different definitions of cities from the point of view of their respective scientific orientations.